The Effect of Audit Quality, Managerial Ownership, And Audit Committee on The Integrity of Financial Statements (Empirical Study on Manufacturing Companies Listed on The IDX 2015-2019) - Nur Isna Inayati; Siti Nur Azizah (ITB AAS INDONESIA, 2021)
This study aims to examine the effect of audit quality, managerial ownership and audit committee on the integrity of financial statements. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Sampling in this study using purposive sampling method, and obtained 235 samples from 47 manufacturing companies from 2015-2019. The data analysis technique used is the logistic regression analysis method. The results of this study indicate that audit quality has a negative effect on the integrity of financial statements. Meanwhile, the audit committee and managerial ownership have no effect on the integrity of the financial statements.